EFEKTIVITAS TEMA KEPARIWISATAAN DALAM PENDIDIKAN DAN PELATIHAN KEPEMIMPINAN TINGKAT II PROVINSI BALI DALAM PENGEMBANGAN KEPEMIMPINAN ADAPTIF - Nyoman Sukamara (Lembaga Administrasi Negara, 2018)
Tourism Thematic of Level II Leadership Training and Education organized by the Agency for Human Resource Development of Bali Province is intended to improve leadership competence as the Regulation of the Head of Nasional Institut Public Administration (NIPA) Number 15 Year 2015 which also has a tourism mindset, which ultimately increases the competence of adaptive leadership. The question in this study is how is the effectiveness of the theme of tourism in improving managerial competence and adaptive leadership? By using qualitative descriptive explanatory analysis method can be concluded learning process of thematic training of tourism effective in developing competency of adaptive leadership of training participants with some things that still need to be improved. Furthermore, it can be recommended to prepare the standard implementation of Thematic Leadership Level II Training of Tourism, which provides reinforcement of substance and material insertion process of tourism into the existing curriculum according to Regulation of the Head of NIPA Number 15 Year 2015 Number 15 Year 2015. Keywords: training, tourism, adaptive leadership